“Now Is the Time to Start Reconciliation, and We Are the People to Do So”, Walking the Path of an Anti-Racist White Ally - Margot Hurlbert (Societies, 2022)
Media accounts of hundreds of unmarked graves of children at the sites of residential schools in Canada in 2021 is one more urgent call for all Canadians to start walking the path for reconciliation, decolonization, and anti-racism. In this exploratory reflection utilizing hermeneutical phenomenology, my journey to reconciliation is described. Through a review of Indigenous law and sovereignty, Canadian numbered treaties, and residential schools, this article explores justice, discovering the truth, and advancing reconciliation. In order to achieve justice, first ethnocentrism, or our evaluation of Indigenous cultures according to our preconceived preference for our own standards and customs, must be recognized, exposed, and set aside. Without our own ethnocentric attachment, and consequently with an open mind, we can hear the truth of Indigenous peoples and internalize it. Examples include the truth of the treaties and residential schools. The reconciliation path entails pursuing justice; this includes recognizing both Indigenous sovereignty and Indigenous law. This path doesn’t ‘restore’ relations historically, but does build reconciliation for the future. However, the process will not be comfortable. The reward will be a more equitable and inclusive society.